Cadmium Suppresses Bone Marrow Thrombopoietin Production and Impairs Megakaryocytopoiesis in Mice. (3rd February 2022) - Zhao, Yifan; Zhang, Yufan; He, Jinyi; Zhai, Yue; Yang, Guangrui; Xue, Peng; Yao, Ye; He, Miao; Qu, Weidong; Zhang, Yubin
Abstract: Cadmium (Cd) is a highly toxic heavy metal in our environment. The influence of Cd on the development of platelets, or megakaryocytopoiesis, remains to be defined. The aim of this study was to investigate the impact of Cd on megakaryocytopoiesis. C57BL/6 (B6) mice aged 6–8 weeks were treated with 10 ppm Cd via drinking water or control for 3 months, and megakaryocytopoiesis was evaluated thereafter. Mice treated with Cd had a decreased number of platelets in the blood, which was associated with the reduced number of megakaryocyte progenitors (MkP) and megakaryocytes (MK) in the bone marrow (BM). Functional analyses indicate that Cd treatment impaired the proliferation and differentiation of MkP as well as the maturation of MK in the BM, suggesting that Cd treatment impeded megakaryocytopoiesis. Intriguingly, the impaired megakaryocytopoiesis in the BM of mice treated with Cd was not caused by increased apoptosis of MkP. Moreover, in vitro treatment of MkP with Cd did not impact their proliferation or differentiation, indicating that the impeded megakaryocytopoiesis in the BM of mice was likely not caused by direct action of Cd on MkP. On the other hand, Cd treatment selectively suppressed thrombopoietin (TPO) production in the BM and decreased the cellular myelocytomatosis oncogene signaling in MkP, thus likely leading to the impeded megakaryocytopoiesis in the BM and thrombocytopenia in the blood of mice. This study revealed a previously unrecognized hematopoietic toxicity of Cd, which may extend our current understanding of Cd toxicity.